2021
DOI: 10.1007/s00394-021-02737-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed food intake is associated with grip strength decline in middle-aged and older adults: a prospective analysis of the TCLSIH study

Abstract: Purpose Ultra-processed foods make up more than 50% of daily energy consumed in Western countries and are rapidly increasing in China. However, little is known about the association between ultra-processed food intake and muscle strength, a predictor for physical disability in senior years. We aimed to investigate the association of ultra-processed food intake with longitudinal changes in grip strength among middle-aged and older Chinese adults. Methods This prospective cohort study included a total of 5409 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Adjustment for further covariates including a healthy diet score (based on fruit, vegetable, unprocessed red meat and fish intake), dietary supplement use and protein and milk intake did not alter the association, with each 10% increment in UPF intake still associated with −0.32 kg (−0.53, −0.11) and −0.0046 kg/kg weight (−0.0076, −0.0016) yearly reductions in absolute and weight-adjusted grip strength, respectively [138].…”
Section: Review Of Prospective Studies Adjusting For Dietary Qualitymentioning
confidence: 81%
See 3 more Smart Citations
“…Adjustment for further covariates including a healthy diet score (based on fruit, vegetable, unprocessed red meat and fish intake), dietary supplement use and protein and milk intake did not alter the association, with each 10% increment in UPF intake still associated with −0.32 kg (−0.53, −0.11) and −0.0046 kg/kg weight (−0.0076, −0.0016) yearly reductions in absolute and weight-adjusted grip strength, respectively [138].…”
Section: Review Of Prospective Studies Adjusting For Dietary Qualitymentioning
confidence: 81%
“…In a separate study, Zhang et al reported that each 10% increment in UPF in the diet was associated with a −0.30 kg (−0.50, −0.09) and −0.0043 kg/kg weight (−0.0073, −0.0014) yearly reduction in absolute and weight-adjusted grip strength, respectively [138].…”
Section: Review Of Prospective Studies Adjusting For Dietary Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to UP being usually rich in energy, saturated fats, sugar, and salt (Monteiro et al, 2018a;Rauber et al, 2018), they also have lower protein content than in natura/minimally processed foods, so UP also have been associated with lower protein intake (Martínez Steele et al, 2018;Rauber et al, 2018). To our knowledge, reports relating UP consumption and muscle health, especially in older adults with sarcopenia, are lacking in the literature (Sandoval-Insausti et al, 2020;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%